2017
DOI: 10.1002/mrm.26811
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic assessment of a migraine model using relaxation‐enhanced 1H spectroscopy at ultrahigh field

Abstract: These changes indicate an altered metabolic profile in the migraine analogue consistent with early changes in neural activity and/or vasodilation consistent with progressively enhanced neuroprotection and osmoregulation. Magn Reson Med 79:1266-1275, 2018. © 2017 International Society for Magnetic Resonance in Medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 63 publications
2
7
0
Order By: Relevance
“…Examples of the mitochondrial effects of nitric oxide in animals include inhibition of the mitochondrial respiratory chain in cultured astro cytes 242 . By contrast, use of 1 H MRS in rats has shown that cortical lactate increases as early as 10 min after intraperitoneal injection of nitroglycerin, suggesting that the widely used nitroglycerin model of migraine involves metabolic, in addition to vascular, changes 243 .…”
Section: Trigeminovascular Systemmentioning
confidence: 90%
“…Examples of the mitochondrial effects of nitric oxide in animals include inhibition of the mitochondrial respiratory chain in cultured astro cytes 242 . By contrast, use of 1 H MRS in rats has shown that cortical lactate increases as early as 10 min after intraperitoneal injection of nitroglycerin, suggesting that the widely used nitroglycerin model of migraine involves metabolic, in addition to vascular, changes 243 .…”
Section: Trigeminovascular Systemmentioning
confidence: 90%
“…This excitation yielded maximum signal for a repetition time (TR) of 180 ms and effective dwell time (time between the end of excitation and start of acquisition) less than 660 μs. Six averages yielded a total of 3000 repetitions for the complete data acquisition of a single slice, which permitted the complete dataset for four slices to be acquired in nine minutes and corresponds to the time course of a previous study that assessed metabolic changes in NTG-triggered rats [1] while still yielding a sodium SNR in excess of 30:1.…”
Section: Methodsmentioning
confidence: 99%
“…Migraine is accompanied with a complex chain of biochemical changes in the CSF and brain which may contribute, together with sodium, to regulation of water movement across the BCSFB. For instance, it has been shown that CSF (and plasma) content of organic osmolytes, such as taurine and glutamate, which can significantly regulate brain cell volume homeostasis (Schousboe and Pasantes-Morales, 1992;Fisher et al, 2008), changes during migraine (Martinez et al, 1993;Cananzi et al, 1995;van Dongen et al, 2017;Abad et al, 2018b). However, it is yet to be determined how the variations in organic osmolyte levels can influence the osmotically driven water transport across the BCSFB.…”
Section: Discussionmentioning
confidence: 99%